Close management of sheep in ancient Central Asia: evidence for foddering, transhumance, and extended lambing seasons during the Bronze and Iron Ages. Issue 1 (1st January 2020) - Ventresca Miller, A. R.; Haruda, A.; Varfolomeev, V.; Goryachev, A.; Makarewicz, C. A.
ABSTRACT: Pastoralism in Central Asia directed the utilization of natural resources, yet information on livestock management strategies remain scarce. Carbon (δ 13 C) and oxygen (δ 18 O) isotope analyses of domesticated sheep teeth are used to identify animal management strategies. Sheep from Kent exhibit an inverserelationship where low δ 18 O values coincide with high δ 13 C values, consistent with the foddering of caprines in the winter for this location which occursalongside evidence for an extended lambing season. At the high altitude encampment of Turgen, Bronze Age sheep exhibit low δ 18 O values that coincide withhigh δ 13 C values, suggesting that livestock were moved to low altitude pastures in the winter months. Iron Age sheep sequences also have an inverserelationship, where low δ 18 O values coincide with high δ 13 C values, yet high δ 13 C values in the winter suggest that livestock were foddered. Our findingsindicate variation in livestock management strategies with distinct adaptations to local ecologies.